Positive electrode-diaphragm synergistic lithium-rich manganese-based solid-state lithium ion battery and preparation method thereof

By applying relaxed ferroelectric materials and piezoelectric materials on the positive electrode and separator of lithium-rich manganese-based solid-state batteries, the physical and chemical adaptation coordination between the positive electrode and separator is achieved, and the problem of poor capacity and cycle stability of lithium-rich manganese-based solid-state batteries in solid-state battery systems is solved, and the electrochemical performance of the battery is significantly improved, especially under low temperature conditions.

CN118472350BActive Publication Date: 2025-04-04广东聚圣科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410313968.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-19
Publication Date
2025-04-04
Estimated Expiration
2044-03-19

AI Technical Summary

Technical Problem

Lithium-rich manganese-based solid-state batteries have problems with poor capacity and cycle stability in solid-state battery systems, especially under low temperature conditions.

Method used

By applying relaxed ferroelectric material modified lithium-rich manganese-based active materials and piezoelectric material modified separators on the positive electrode and the separator, the physical and chemical adaptation synergy between the positive electrode and the separator is achieved and the electrochemical performance is improved.

Benefits of technology

The capacity, long-range cycle stability and low-temperature cycle stability of lithium-rich manganese-based solid-state batteries have been significantly improved, and the problem of lithium-rich manganese-based materials are easily deteriorated in solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118472350B_ABST
    Figure CN118472350B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of solid-state batteries, and specifically relates to a positive electrode-diaphragm synergistic lithium-rich manganese-based solid-state lithium-ion battery, including a battery cell that is sequentially composited by a positive electrode, a diaphragm and a negative electrode, and a solid or semi-solid electrolyte arranged on the surface and between layers of the battery cell; the positive electrode includes a current collector and a positive electrode material composited on its surface, the positive electrode material includes a conductive agent, a binder A and a positive electrode active material, wherein the positive electrode active material includes a lithium-rich manganese-based active material modified by a relaxor ferroelectric material; the diaphragm includes a base film and a modified layer composited on its surface, the modified layer includes a binder B and a piezoelectric material. The present invention also relates to a method for preparing the battery. The present invention can adapt and synergize through the combination of the positive electrode and the diaphragm, and can significantly improve the capacity and long-range cycle stability of the lithium-rich manganese-based solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials and battery manufacturing, and in particular to the technical field of lithium-rich manganese-based solid-state batteries. Background Art

[0002] At present, lithium-ion batteries have been fully integrated into our lives, such as portable electronic devices, electric vehicles, energy storage and other fields. However, lithium-ion batteries at this stage have fallen into the bottleneck of energy density, and new battery technologies must be developed to meet the energy density requirements. The lithium-rich manganese-based positive electrode has the advantages of high capacity, high voltage and low cost, and is one of the most promising positive electrode materials for the next generation of high-energy-density batteries.

[0003] However, the electrical conductivity of the lithium-rich manganese-based positive electrode material itself is not ideal, and it is difficult to effectively exert high capacity and stability. In addition, it is difficult to match the physical and chemical structure characteristics of the solid electrolyte. Making lithium-rich manganese-based materials into solid-state batteries will further increase the intrinsic disadvantages of the lithium-rich manganese-based positive electrode, further deteriorating the rate performance and cycle stability of the lithium-rich manganese-based solid-state battery, limiting its application in solid-state battery systems.

[0004] In view of the shortcomings of lithium-rich manganese-based solid-state batteries, the existing improvement ideas mainly lie in the innovation of positive electrodes or solid electrolytes. For example, for the positive electrode, the publication number CN117542974A discloses a sheet-like radiation-type lithium-rich material, the interior of the sheet-like radiation-type lithium-rich material is a hollow structure, and the primary particles are continuous radial radiation from the inside to the outside, and the radiation length is 0.5-3um. The Chinese patent with the publication number CN117410463A discloses a composite positive electrode material for sulfide solid-state batteries. The composite positive electrode material is a mixed solution method to generate an interface buffer layer of Li-TM-OSP (TM = Ni, Co, Mn) on the surface of the positive electrode active material particles, and in situ growth of crystalline sulfide in the gap between the particles and the interface buffer layer to form a three-dimensional ion composite positive electrode active material.

[0005] For another example, with respect to solid electrolytes, a Chinese patent document with publication number CN117254102A discloses a highly safe solid electrolyte and a solid-state battery thereof, wherein the solid electrolyte comprises a lithium salt, an organic solvent and a thermosetting additive; and the thermosetting additive comprises a polymer monomer and an initiator.

[0006] In summary, for lithium-rich manganese-based solid-state batteries, the main existing improvement ideas lie in the modification of the positive electrode or solid electrolyte, and there are relatively few improvements on the diaphragms of lithium-rich manganese-based solid-state batteries; not only that, the existing technology also has relatively few improvement ideas based on the combined synergistic enhancement of lithium-rich manganese-based positive electrodes and diaphragms. Summary of the invention

[0007] In view of the problems that lithium-rich manganese-based positive electrode materials are difficult to adapt to the application requirements of solid-state batteries, and the capacity and cycle stability of lithium-rich manganese-based solid-state batteries are not ideal, the first purpose of the present invention is to provide a positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery, aiming to improve the capacity and high-rate cycle stability caused by the intrinsic defects of lithium-rich manganese-based batteries through the coordinated control of the positive electrode sheet and the diaphragm.

[0008] The second object of the present invention is to provide a method for preparing the positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery.

[0009] In view of the problems that the intrinsic physical and chemical characteristics of lithium-rich manganese-based materials easily lead to aggravated degradation in solid-state battery systems, and the capacity, cycle stability, especially low-temperature stability are not ideal, the present invention has provided the following improvement scheme after in-depth research:

[0010] A positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery, comprising a battery cell that is sequentially composited by a positive electrode, a separator and a negative electrode, and a solid or semi-solid electrolyte arranged on the surface and between layers of the battery cell; the positive electrode comprises a current collector and a positive electrode material composited on its surface, the positive electrode material comprises a conductive agent, a binder A and a positive electrode active material, wherein the positive electrode active material comprises a lithium-rich manganese-based active material modified by a relaxor ferroelectric material;

[0011] The diaphragm comprises a base film and a modified layer compounded on the surface thereof, and the modified layer comprises a binder B and a piezoelectric material.

[0012] In order to better solve the problem that lithium-rich manganese-based materials are prone to aggravated degradation in solid-state batteries, the present invention provides a new solution based on the combined synergy of the positive electrode and the diaphragm, and innovative research shows that through the combination of the lithium-rich manganese-based active material positive electrode modified by the relaxor ferroelectric material and the diaphragm modified by the piezoelectric material described in the present invention, the physical and chemical adaptation and synergy between the positive electrode and the diaphragm can be unexpectedly achieved, thereby significantly solving the problem that lithium-rich manganese-based materials are prone to degradation in solid-state battery systems, and significantly improving the capacity and long-range cycle stability, especially low-temperature cycle stability, of lithium-rich manganese-based solid-state batteries.

[0013] In the present invention, the relaxor ferroelectric material modified lithium-rich manganese-based active material is relaxor ferroelectric material A x Li (1-x) BO3 in-situ coated lithium-rich positive electrode active material; wherein the A includes at least one of La, Ce, Nd, and Bi; the B includes at least one of Ta, Nb, W, Zr, and Ti; and the x is 0.85 to 0.99.

[0014] In the present invention, the relaxor ferroelectric material A x Li (1-x)The preparation method of the BO3 in-situ coated lithium-rich positive electrode active material is as follows: compounding the A source compound, the B source compound and the lithium-rich positive electrode material and sintering them at 400-700° C. to obtain.

[0015] The research of the present invention shows that, through the innovative preparation method, the lithium in the lithium-rich manganese-based material can be used to in-situ participate in the sintering and lithiation modification of the relaxor ferroelectric material, which can effectively improve the interface effect between the coating layer and the bulk phase, improve the lithium conduction pathway, and further combine it with the modified diaphragm described in the present invention, which can unexpectedly further enhance the compatibility and synergy of the positive electrode and the diaphragm, and further improve the electrochemical performance of the lithium-rich manganese-based solid-state battery.

[0016] The lithium-rich manganese-based material may be a component known in the industry, for example, as a typical example, its expression is Li a Mn b Ni c Co d O2; 1 of them<a≤1.5;0.4≤b≤0.8;0≤c≤0.4;0≤d≤0.4;b> c>d.

[0017] In the present invention, the molar ratio of the source compound A to the lithium-rich manganese-based material can be adjusted as needed, for example, it can be 0.01 to 0.3:1, and further can be 0.05 to 0.2:1.

[0018] Preferably, the sintering temperature is 550-700°C, more preferably 600-650°C.

[0019] The sintering atmosphere is an oxygen-containing atmosphere, further air or oxygen, preferably oxygen. The present invention shows that the in-situ sintering in an oxygen atmosphere helps to further adjust the phase structure and interlayer structure, so that the prepared material and the diaphragm have more adaptive synergy, which can further improve the low-temperature performance of the prepared solid-state battery.

[0020] Preferably, the sintering time is 3 to 10 hours, and further can be 4 to 6 hours.

[0021] In the present invention, the conductive agent includes at least one of Super P, KS-6, and Ketjen Black;

[0022] In the present invention, the binder A may be a conventional component having bonding ability, for example, at least one of PVDF, P(VDF-TrFE), P(VDF-TrFE-CTFE), and P(VDF-HFP);

[0023] Preferably, in the positive electrode material, the weight ratio of the conductive agent, the binder A and the positive electrode active material is 0.01-0.1: 0.01-0.1: 0.8-0.98; further, it can be 0.02-0.05: 0.01-0.05: 0.9-0.98.

[0024] In the present invention, the modified positive electrode and the modified separator are innovatively combined, which can alleviate the expansion and pulverization of the positive electrode. In addition, it can also be beneficial to the stress improvement hierarchical interface of the two, reduce impedance, and improve the conduction of electrons and ions, thereby synergistically solving the problem that lithium-rich manganese-based materials are difficult to adapt to the requirements of solid-state batteries and improving their performance in solid-state battery systems.

[0025] In the present invention, the piezoelectric material includes at least one of perovskite-type ABO3 piezoelectric material, lithium gallate, lithium germanate, lithium niobate, and lithium tantalate; the A includes at least one of La, Ce, Nd, and Bi; and the B includes at least one of Ta, Nb, W, Zr, and Ti.

[0026] In the present invention, the piezoelectric material includes a lithium-doped perovskite-type ABO3 piezoelectric material. Studies have shown that the diaphragm modified with the piezoelectric material, combined with the special positive electrode, has better adaptability and synergy, which helps to further improve the electrochemical performance of lithium-rich manganese-based batteries.

[0027] In the present invention, in the lithium-doped perovskite-type ABO3 piezoelectric material, A includes at least one of La, Ce, Nd, and Bi; and B includes at least one of Ta, Nb, W, Zr, and Ti.

[0028] In the present invention, the lithium-doped perovskite-type ABO3 piezoelectric material is obtained by mixing a lithium source, a source A, and a source B and then calcining. In the present invention, the molar ratio of Li, A, and B in the lithium source, the source A, and the source B can be 0.01 to 0.3:1:1, and can further be 0.1 to 0.2:1:1. The calcination temperature is, for example, 550 to 700°C, and can further be 600 to 650°C, and further includes two stages of heat treatment, wherein the temperature of the first stage of treatment is 600 to 620°C, and the temperature of the second stage of heat treatment is 640 to 650°C. The calcination atmosphere can be an oxygen-containing atmosphere, and considering the cost, it can be air or oxygen. The calcination time can be 1 to 10 hours, and can further be 3 to 6 hours.

[0029] In the present invention, the binder can be a conventional component with bonding ability. Considering the synergistic treatment of the positive electrode and the separator, the binder B further preferably includes at least one of PVDF, P(VDF-TrFE), P(VDF-TrFE-CTFE), P(VDF-HFP), β-PVDF, β-P(VDF-TrFE), β-P(VDF-HFP); further preferably at least one of β-PVDF, β-P(VDF-TrFE), β-P(VDF-HFP). Studies have shown that the use of the preferred binder B, in combination with the piezoelectric material, can have a better synergistic strengthening effect with the positive electrode, can solve the impedance of the hierarchy, reduce the interface side reaction, and further synergistically improve the electrochemical performance of the prepared lithium-rich manganese-based battery.

[0030] In the present invention, in the modified layer, the weight ratio of the binder B to the ferroelectric material is 0.01-0.2:0.8-0.99, and can further be 0.05-0.15:0.85-0.95;

[0031] Preferably, in the diaphragm, the base film includes at least one of PP and PE.

[0032] In the present invention, the preparation steps of the diaphragm are as follows: PVDF, DMF and piezoelectric material are slurried and then coated on a base film, and then heated for in-situ transformation to obtain the diaphragm.

[0033] In the present invention, through the in-situ preparation process, the in-situ transformation of the crystal structure of PVDF can be achieved, which helps to improve the interface effect between piezoelectric materials and improve the ion and electron conduction behavior, thereby further strengthening the physicochemical synergy between it and the positive electrode and further improving the electrochemical performance of the lithium-rich slam battery.

[0034] In the present invention, the in-situ transformation process includes two heat treatment processes; wherein the temperature of the first stage is 60-65°C; the temperature of the second stage is 70-75°C. Furthermore, the air pressure of the first stage is atmospheric pressure, and the pressure of the second heat treatment is 0.05-0.5atm (atm refers to atmospheric pressure). Studies have shown that the use of the two-stage heat treatment, further combined with the joint control of the pressure of the two-stage heat treatment, can further improve the interface structure of the material, and can further cooperate with the positive electrode, which helps to further improve the performance of the prepared battery, especially the low-temperature cycle stability.

[0035] In the present invention, in the solid-state battery, except for the coordinated positive electrode and separator described in the present invention, the other component components, structures, and material types can be conventional.

[0036] In the present invention, the electrolyte includes one or more of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0037] For example, the electrolyte may be a conventional polymer solid electrolyte, which may be a precursor solution containing a monomer, a monomer polymerization aid, and a basic electrolyte obtained by polymerization by an in-situ or non-in-situ method. The monomer may be any monomer that can be used to form a solid electrolyte that is permitted in the industry, such as an acrylic monomer. The auxiliary agent may, for example, be a component that assists the polymerization of the monomer, such as an initiator, a cross-linking agent, etc. The basic electrolyte may be a conventional liquid electrolyte in the industry, such as a solution containing a conductive lithium salt and a solvent.

[0038] The negative electrode of the present invention may be any negative electrode known in solid-state batteries, for example, a graphite negative electrode, a silicon-carbon negative electrode, a silicon-oxygen negative electrode, a metal lithium negative electrode or a current collector negative electrode;

[0039] There is no special requirement for the type of the positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery, for example, it can be a soft pack, cylindrical, square or button type.

[0040] In the present invention, the positive electrode and the separator can be combined to form a solid-state battery based on known processes and methods.

[0041] The present invention also provides a method for preparing the positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium ion battery, which is obtained by compounding the positive electrode, the diaphragm, the negative electrode, and the solid electrolyte.

[0042] The present invention also provides an in-situ preparation method, the steps of which are: obtaining the positive electrode and the separator, then combining the positive electrode, the separator and the negative electrode to form a battery core, placing the battery core in a battery shell, injecting a precursor solution of a solid electrolyte, and in-situ curing after packaging.

[0043] Beneficial Effects

[0044] The present invention innovatively combines a lithium-rich manganese-based active material positive electrode modified by a relaxor ferroelectric material and a diaphragm modified by a piezoelectric material, which can unexpectedly achieve physical and chemical adaptation and coordination between the positive electrode and the diaphragm, thereby significantly solving the problem of easy degradation of lithium-rich manganese-based materials in solid-state battery systems, and significantly improving the capacity, long-range cycle, and especially low-temperature cycle stability of lithium-rich manganese-based solid-state batteries.

[0045] In the present invention, the lithium-rich manganese-based active material of the positive electrode, the binder in the diaphragm and the piezoelectric material are further jointly controlled, which can unexpectedly further enhance the synergistic effect between the positive electrode and the diaphragm, further improve the interface effect in the solid-state battery, reduce impedance and interfacial side reactions, and thus synergistically improve the electrochemical performance of the lithium-rich manganese-based solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The performance diagram of Example 1 and Comparative Example 1 at 5C rate;

[0047] Figure 2 The cycle diagram of Example 1 and Comparative Example 1 at 1C and 25°C;

[0048] Figure 3 The cycle diagram of Example 1 and Comparative Example 1 at 1C and -20°C; DETAILED DESCRIPTION

[0049] A positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery, comprising a battery cell that is sequentially composited by a positive electrode, a separator and a negative electrode, and a solid or semi-solid electrolyte arranged on the surface and between layers of the battery cell; the positive electrode comprises a current collector and a positive electrode material composited on its surface, the positive electrode material comprises a conductive agent, a binder A and a positive electrode active material, wherein the positive electrode active material comprises a lithium-rich manganese-based active material modified by a relaxor ferroelectric material;

[0050] The diaphragm comprises a base film and a modified layer compounded on the surface thereof, and the modified layer comprises a binder B and a piezoelectric material.

[0051] The preparation method of the positive electrode of the present invention is, for example:

[0052] (I) Using NMP as solvent, pour the binder PVDF with designed solid content into the NMP solution and stir for 3-6 hours to form a glue solution;

[0053] (II) adding a conductive agent, wherein the conductive agent includes at least one of Super P, KS-6, and Ketjen Black;

[0054] (III) adding a high-conductivity lithium-rich positive electrode material coated with a relaxor ferroelectric material coating in 2-3 batches, stirring for 5-10 minutes after each batch is added, and continuing to stir for 1-3 hours or until all are added to obtain a positive electrode slurry;

[0055] (IV) The positive electrode slurry is coated on the surface of the aluminum foil and dried to obtain a positive electrode sheet.

[0056] The preparation process of the above-mentioned high-lithium-conductivity lithium-rich positive electrode material is: mix the A source compound and the B source compound of the perovskite-type ABO3 relaxor ferroelectric material with the lithium-rich positive electrode material in solid phase or liquid phase, and then sinter at 400-700°C in an oxygen-containing atmosphere for 3-10 hours to obtain a functional lithium-rich positive electrode material coated with a relaxor ferroelectric material.

[0057] The negative electrode sheet is a graphite negative electrode, a silicon-carbon negative electrode, a silicon-oxygen negative electrode, a metal lithium negative electrode or a current collector negative electrode prepared by a conventional method.

[0058] The preparation method of the present invention is, for example:

[0059] (I) pouring a certain amount of PVDF-based polymer into a solvent (such as NMP, DMF, etc.) solution, controlling the concentration of the PVDF solution to 1wt% to 20wt%, and stirring for 2-10 hours to form a glue solution;

[0060] (II) adding piezoelectric material and stirring for 1-5 hours or until uniform;

[0061] (III) coating the slurry on the surface of the PP or PE separator by conventional means such as gravure coating, doctor blade coating, and extrusion coating;

[0062] (IV) The coated diaphragm is placed in an environment of 50 to 80° C. for heat treatment for 4 to 15 hours to obtain a modified diaphragm.

[0063] The above-mentioned solid electrolyte includes one or more of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte, and is preferably a polymer solid electrolyte obtained by an in-situ solidification process.

[0064] For example, as an illustrative scheme, in the following case, the selected solid electrolyte is obtained by in-situ or non-in-situ polymerization of the precursor solution. The precursor solution is, for example, a basic electrolyte solution in which a monomer (methyl methacrylate) and an additive (such as AIBN) are dissolved, the content of the monomer is 4.5-5wt.%, the content of the additive is 0.3-0.5wt.%, and the basic electrolyte is 1mol / L LiPF6 / ethylene carbonate (EC) / diethyl carbonate (DEC) / dimethyl carbonate (DMC) (volume ratio 1:1:1).

[0065] The above-mentioned other auxiliary materials include necessary auxiliary materials such as tabs, shells, insulating glue, packaging films, etc. required for the production of various types of batteries.

[0066] A method for manufacturing a high-specific-energy and high-rate lithium-manganese-rich solid-state lithium battery based on relaxor ferroelectric materials, that is, according to existing processes, positive electrode plates, negative electrode plates, modified PP or PE separators, solid electrolytes and other auxiliary materials are assembled into batteries. The batteries can be in the form of soft packs, cylinders, squares, button types, etc. The battery production process is the same as the existing process, that is, a stacking process, a winding process, etc. can be used.

[0067] Preferably, when a polymer solid electrolyte using an in-situ solidification process is used, after the battery is assembled, steps such as liquid injection, packaging, standing, high-temperature curing, formation, (secondary curing), secondary sealing, and capacity division need to be performed.

[0068] The following are specific optional implementation plans:

[0069] Embodiment 1:

[0070] Step (1): The method for manufacturing the functional positive electrode sheet is as follows:

[0071] (I) Using NMP as a solvent, pour the binder PVDF into the NMP solution so that PVDF accounts for 1.5% of the total mass of the slurry, and stir for 3 hours to form a glue solution;

[0072] (II) adding a conductive agent (composite conductive carbon material, the composite conductive carbon material includes a mixture of Super P and KS-6 in a mass ratio of 1:1), the composite conductive carbon material accounts for 2% of the total mass of the slurry, and stirring for 2 hours until it is uniform;

[0073] (III) adding lithium-rich active material (high-conductivity lithium-rich positive electrode material coated with a relaxor ferroelectric material coating) in two batches, stirring for 10 minutes after each batch is added, and continuing to stir for 3 hours after all are added until uniform, to obtain a positive electrode slurry;

[0074] The lithium-rich active material is a functional lithium-rich material coated with a composite perovskite-type BiTiO3 relaxor ferroelectric material, which is synthesized by the following steps: Bi(NO3)3·5H2O, C 16 H 36 O4Ti is dissolved in ethanol / water mixture, and then lithium-rich manganese-based materials (Li 1.2 Mn 0.53 Ni 0.27 O2, wherein the molar ratio of Bi, Ti and lithium-rich manganese positive electrode material is 0.05:0.05:1), and then sintered at 650°C for 5 hours in an oxygen atmosphere to obtain a functional lithium-rich positive electrode material (lithium-rich active material) coated with a relaxor ferroelectric material.

[0075] (IV) The positive electrode slurry is coated on the surface of the aluminum foil, and after drying, a positive electrode sheet is obtained (the weight ratio of the binder, the conductive agent, and the lithium-rich active material is 1.5:2:96.5).

[0076] Step (2): The manufacturing method of the modified PP composite diaphragm is as follows:

[0077] (a) Using DMF as a solvent, a certain amount of PVDF-based polymer was poured into a DMF solution, the concentration of the PVDF solution was controlled to be 10 wt %, and stirred for 2 hours to form a gel solution;

[0078] (b) adding a perovskite BiTiO3 relaxor ferroelectric material (piezoelectric material) and stirring for 2 hours or until uniform; wherein the weight ratio of PVDF to the piezoelectric material is 1:9;

[0079] (c) coating the slurry on the surface of the PP diaphragm (base film) by a doctor blade coating method; the coating thickness is 0.9 to 1 times the thickness of the base film;

[0080] (d) The coated diaphragm was placed in an environment of 80° C. and atmospheric pressure for heat treatment for 12 hours to obtain a modified diaphragm.

[0081] Step (3): Assembly:

[0082] Metal lithium is used as the negative electrode.

[0083] Polymer solid electrolyte using in-situ solidification process.

[0084] The above-mentioned other auxiliary materials include tabs, aluminum-plastic film, insulating glue, packaging film, etc.

[0085] Using a stacking machine, lithium-rich metal batteries are assembled based on the stacking process.

[0086] After the battery is assembled, it needs to be filled with liquid and packaged, left to stand at 25°C for 72 hours, and then cured at 60°C for 6 hours. The formation process is to charge at a rate of 0.1C to a cut-off voltage of 4.7V, followed by secondary sealing and capacity division.

[0087] like Figure 1 As shown, the rate performance of the obtained battery at room temperature is better than that of the comparative example, especially at 5C, it releases a capacity of 174 mAh / g. In terms of cycle performance, the initial discharge specific capacity of Example 1 at 1C and 25°C is 238.5 mAh / g, and the capacity retention rate is 88% after 270 cycles. In terms of low-temperature kinetic performance, at -20 degrees and 1C current density, Example 1 releases a capacity of 148 mAh / g, and after 300 cycles, the capacity is 144.3 mAh / g, and the capacity retention rate is 97.8%.

[0088] Example 2 - Changing the positive electrode active material

[0089] Compared with Example 1, the only difference is that the positive electrode active material is changed, specifically, the sintering process of step (III) of step 1 is changed. The experimental groups are:

[0090] Group A: The sintering atmosphere is air, and other operations and parameters are the same as those in Example 1;

[0091] Group B: sintering temperature is 600℃;

[0092] Group C: The sintering process includes two stages of gradient sintering, wherein the first stage is sintered at a temperature of 600°C for 2.5 h, and the second stage is sintered at a temperature of 650°C for 2.5 h.

[0093] Group D: The lithium-rich active material is not prepared by the in-situ preparation method, but is replaced by a physical mixture of BiTiO3 and lithium-rich manganese-based material, the proportion of which is the same as in Example 1;

[0094] The test was carried out according to the method of Example 1, and the results were:

[0095] A: 164 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 225.6 mAh / g, and the capacity retention rate is 84% ​​after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 139 mAh / g, and the capacity retention rate is 94.6% after 300 cycles.

[0096] B: 162 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 220.9 mAh / g, and the capacity retention rate is 83% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 136 mAh / g, and the capacity retention rate is 92.9% after 300 cycles.

[0097] C: 175 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 239.2 mAh / g, and the capacity retention rate is 89% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 150 mAh / g, and the capacity retention rate is 98.7% after 300 cycles.

[0098] D: 159 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 212.3 mAh / g, and the capacity retention rate is 80% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 125 mAh / g, and the capacity retention rate is 86.3% after 300 cycles.

[0099] It can be seen from Examples 1 and 2 that by adopting the in-situ encapsulation process, the lithium in the lithium-rich manganese base can be utilized to participate in the construction of the coating structure, which is beneficial to improve the interface effect, improve the conduction network and pathway of lithium and electrons, and thus unexpectedly improve its low-temperature performance.

[0100] Example 3 - Changing the composition of the membrane:

[0101] Compared with Example 1, the only difference is that the diaphragm in step (2) is changed. The experimental groups are:

[0102] Group A: The binder was changed to non-in-situ β-PVDF, that is, PVDF was directly replaced with an equal amount of β-PVDF, and the solvent of step 2 (a) was NMP;

[0103] Group B: The binder is amorphous β-PVDF, that is, the solvent in step 2 (a) is changed to NMP;

[0104] Group C: In control (2) (d), the gas pressure during the heat treatment process was 0.2 atm, and the other operations and parameters were the same as those in Example 1;

[0105] Group D: In (2) (d), two heat treatments were performed, wherein the first heat treatment was performed at a temperature of 60°C, a time of 2 h, and an atmospheric pressure, and the second heat treatment was performed at a temperature of 80°C, a pressure of 0.2 atm, and a time of 10 h. Other operations and parameters were the same as those in Example 1;

[0106] Group E: The piezoelectric material is changed to a lithium-doped material, which is prepared by using Bi(NO3)3·5H2O, C 16 H 36 O4Ti and lithium carbonate are sintered to obtain lithium-doped piezoelectric material Bi 0.9 Li 0.1 TiO3, the sintering temperature is 600-650°C, and the sintering time is 7-8h; the amount of piezoelectric material and other operations are the same as in Example 1.

[0107] Group F: The steps are the same as those in Example 1, except that lithium niobate piezoelectric material is selected;

[0108] The test was carried out according to the method of Example 1, and the results were:

[0109] A: 161 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 219.7 mAh / g, and the capacity retention rate is 84% ​​after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 137 mAh / g, and the capacity retention rate is 91.1% after 300 cycles.

[0110] B: 158 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 213.3 mAh / g, and the capacity retention rate is 80% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 131 mAh / g, and the capacity retention rate is 90.4% after 300 cycles.

[0111] C: 176 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 239.6 mAh / g, and the capacity retention rate is 89% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 149 mAh / g, and the capacity retention rate is 97.6% after 300 cycles.

[0112] D: 179 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 239.9 mAh / g, and the capacity retention rate is 91% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 151 mAh / g, and the capacity retention rate is 98.9% after 300 cycles.

[0113] E: 178 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 238.6 mAh / g, and the capacity retention rate is 89% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 149 mAh / g, and the capacity retention rate is 98.3% after 300 cycles.

[0114] F: 163 mAh / g capacity is released at 5C, the initial discharge specific capacity at 1C is 220.8 mAh / g, and the capacity retention rate is 84.6% after 270 cycles at 1C and 25°C. At -20 degrees and 1C current density, the released capacity is 141 mAh / g, and the capacity retention rate is 94.5% after 300 cycles.

[0115] It can be seen from Examples 1 and 3 that the use of β-PVDF as a binder, especially β-PVDF based on in-situ crystallization of PVDF-DMF, can improve the synergistic performance of the modified diaphragm and the modified positive electrode. On the basis of the in-situ crystallization, further coordinating the temperature mechanism and pressure control of the heat treatment stage can unexpectedly further improve the adaptive synergistic effect of the prepared diaphragm and the positive electrode, further improve the interface physicochemical structure, reduce interface side reactions and impedance, and thereby improve its low-temperature performance.

[0116] Embodiment 3:

[0117] Compared with Example 1, the only difference is that, in terms of the positive electrode, the coating material of the active material is changed to PbTiO3. That is, in the preparation process, lead nitrate is used to replace the bismuth nitrate, wherein the molar ratio of Pb to Bi is the same. Other operations and parameters are the same as in Example 1.

[0118] The obtained battery released a capacity of 153 mAh / g at 5C, an initial discharge capacity of 214.5 mAh / g at 1C, and a capacity retention rate of 81% after 270 cycles at 1C and 25°C. At -20°C and 1C current density, the initial capacity was 132 mAh / g and the capacity retention rate was 92.1%.

[0119] Embodiment 4:

[0120] Compared with Example 1, the only difference is that the piezoelectric material used in the diaphragm coating is PbNbO3. The obtained battery releases a capacity of 155 mAh / g at 5C, an initial discharge capacity of 216.1 mAh / g at 1C, and a capacity retention rate of 82% after 270 cycles at 1C and 25°C. At -20°C and 1C current density, the initial capacity is 134 mAh / g and the capacity retention rate is 92.7%.

[0121] By comparing Example 1, Example 3 and Example 4, the positive electrode adopts bismuth titanate and the bismuth titanate used in the diaphragm can further achieve synergy, obtain a better adaptive synergistic effect of the positive electrode and the diaphragm, and obtain better electrochemical performance, especially low-temperature performance.

[0122] Comparative Example 1:

[0123] Compared with Example 1, the only difference is that the positive electrode active material adopts the lithium-rich manganese-based material of Example 1 (without in-situ formation of BiTiO3 coating material). The separator adopts a pure PP separator.

[0124] The obtained battery released a capacity of 144 mAh / g at 5C, an initial discharge capacity of 205 mAh / g at 1C, and a capacity retention rate of 83% after 270 cycles at 1C and 25°C. At -20°C and 1C current density, the initial capacity was 103 mAh / g and the capacity retention rate was 47.6%.

[0125] Comparative Example 2:

[0126] Compared with Example 1, the only difference is that the positive electrode active material is changed, which is specifically the positive electrode active material described in Comparative Example 1. Other operations and parameters are the same as in Example 1.

[0127] The obtained battery released a capacity of 151 mAh / g at 5C, an initial discharge capacity of 207.5 mAh / g at 1C, and a capacity retention rate of 82% after 270 cycles at 1C and 25°C. At -20°C and 1C current density, the initial capacity was 116 mAh / g and the capacity retention rate was 82.3%.

[0128] Comparative Example 3:

[0129] Compared with Example 1, the only difference is that the diaphragm is a pure PP diaphragm.

[0130] The obtained battery released a capacity of 148 mAh / g at 5C, an initial discharge capacity of 211.5 mAh / g at 1C, and a capacity retention rate of 80% after 270 cycles at 1C and 25°C. At -20°C and 1C current density, the initial capacity was 118 mAh / g and the capacity retention rate was 87.9%.

Claims

1. A positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery, comprising a battery cell that is sequentially composited with a positive electrode, a separator and a negative electrode, and a solid or semi-solid electrolyte disposed on the surface of the battery cell and between layers; characterized in that: The positive electrode comprises a current collector and a positive electrode material composited on the surface thereof, wherein the positive electrode material comprises a conductive agent, a binder A and a positive electrode active material, wherein the positive electrode active material comprises a lithium-rich manganese-based active material modified by a relaxor ferroelectric material; The relaxor ferroelectric material modified lithium-rich manganese-based active material is relaxor ferroelectric material A x Li (1-x) BO3 in-situ coated lithium-rich positive electrode active material; wherein the A comprises at least one of La, Ce, Nd, and Bi; the B comprises at least one of Ta, Nb, W, Zr, and Ti; and the x is 0.85 to 0.99; The diaphragm includes a base film and a modified layer compounded on the surface thereof, and the modified layer includes a binder B and a piezoelectric material; The piezoelectric material includes at least one of perovskite-type ABO3 piezoelectric material, lithium gallate, lithium germanate, lithium niobate, and lithium tantalate; the A includes at least one of La, Ce, Nd, and Bi; and the B includes at least one of Ta, Nb, W, Zr, and Ti.

2. The positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: The relaxor ferroelectric material A x Li (1-x) The preparation method of the BO3 in-situ coated lithium-rich positive electrode active material is as follows: compounding the A source compound, the B source compound and the lithium-rich positive electrode material and sintering them at 400-700° C. to obtain.

3. The positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 2, characterized in that: The sintering atmosphere is an oxygen-containing atmosphere.

4. The positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 2, characterized in that: The sintering atmosphere is air or oxygen.

5. The positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 2, characterized in that: The sintering time is 3~10h.

6. The positive electrode-diaphragm synergistic lithium-rich manganese-based solid-state lithium-ion battery according to any one of claims 1 to 5, characterized in that: The conductive agent includes at least one of Super P, KS-6 and Ketjen Black.

7. The positive electrode-separator synergistic lithium-rich manganese-based solid-state lithium-ion battery according to any one of claims 1 to 5, characterized in that: The binder A includes at least one of PVDF, P (VDF-TrFE), P (VDF-TrFE-CTFE), and P (VDF-HFP).

8. The positive electrode-separator synergistic lithium-rich manganese-based solid-state lithium-ion battery according to any one of claims 1 to 5, characterized in that: In the positive electrode material, the weight ratio of the conductive agent, the binder A and the positive electrode active material is 0.01-0.1:0.01-0.1:0.8-0.

98.

9. The positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: The piezoelectric material includes lithium-doped perovskite-type ABO3 piezoelectric material.

10. The positive electrode-separator synergistic lithium-rich manganese-based solid-state lithium-ion battery according to claim 1 or 9, characterized in that: The binder B includes at least one of PVDF, P(VDF-TrFE), P(VDF-TrFE-CTFE), P(VDF-HFP), β-PVDF, β-P(VDF-TrFE), and β-P(VDF-HFP).

11. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 10, characterized in that: In the modified layer, the weight ratio of the binder B to the ferroelectric material is 0.01-0.2:0.8-0.

99.

12. The positive electrode-separator synergistic lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: In the diaphragm, the base film includes at least one of PP and PE.

13. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: The preparation steps of the diaphragm are as follows: PVDF, DMF and piezoelectric material are slurried and then coated on a base film, and then heated for in-situ transformation to obtain the diaphragm.

14. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 13, characterized in that: The in-situ transformation process includes two heat treatment processes; wherein the temperature of the first stage is 60-65°C; and the temperature of the second stage is 70-75°C.

15. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: The electrolyte includes one or more of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

16. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 15, characterized in that: The solid electrolyte is prepared by an in-situ or non-situ method.

17. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: The negative electrode is a graphite negative electrode, a silicon-carbon negative electrode, a silicon-oxygen negative electrode, a metal lithium negative electrode or a current collector negative electrode.

18. The positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to claim 1, characterized in that: The positive electrode-separator synergistic lithium-rich manganese-based solid-state lithium-ion battery is in the form of a soft pack, cylindrical, square or button type.

19. A method for preparing a positive electrode-diaphragm coordinated lithium-rich manganese-based solid-state lithium-ion battery according to any one of claims 1 to 18, characterized in that: The positive electrode, the separator, the negative electrode and the solid electrolyte are compounded to obtain the product.

20. A method for in-situ preparation of a positive electrode-separator coordinated lithium-rich manganese-based solid-state lithium-ion battery according to any one of claims 1 to 18, characterized in that: The positive electrode and the separator are obtained, and then the positive electrode, the separator and the negative electrode are combined to form a battery core, the battery core is placed in a battery shell, a precursor solution of a solid electrolyte is injected, and the battery core is cured in situ after packaging.

Citation Information

Patent Citations

  • High-safety solid electrolyte and solid-state battery thereof

    CN117254102A

  • Composite positive electrode material for sulfide solid-state battery as well as preparation method and application of composite positive electrode material

    CN117410463A

  • Flaky radiation type lithium-rich material, preparation method and application in high-voltage solid-state battery

    CN117542974A

  • Lithium-rich manganese-based solid-state lithium battery and preparation method thereof

    CN118213598A